2020
DOI: 10.1111/aas.13724
|View full text |Cite
|
Sign up to set email alerts
|

The effect of remote ischaemic preconditioning on endothelial function after hip fracture surgery

Abstract: The endothelium has a central regulative role in maintaining vascular homeostasis. 1 Besides controlling the vascular tone, it has an anti-inflammatory, anti-thrombotic and anti-fibrinolytic systemic effect. 1,2 Clinical studies in non-cardiac surgery have shown that surgery causes a state of acute endothelial dysfunction lasting for days after the surgical procedure. 3,4 The extent of endothelial dysfunction after surgery seems to be influenced by perioperative factors such as type of surgery, anaesthetics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, seven trials reporting continuous bleeding data as median with range or interquartile range were excluded. [20][21][22][23][24][25][26] Accordingly, 32 randomized controlled trials reporting one or more bleeding outcomes were included (►Fig. 1), with an aggregate of 3,804 patients (1,897 randomized to RIC and 1,907 to control).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, seven trials reporting continuous bleeding data as median with range or interquartile range were excluded. [20][21][22][23][24][25][26] Accordingly, 32 randomized controlled trials reporting one or more bleeding outcomes were included (►Fig. 1), with an aggregate of 3,804 patients (1,897 randomized to RIC and 1,907 to control).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of RIPC on RHI has been investigated in one other trial with patients undergoing subacute hip fracture surgery, where endothelial function was assessed as a point-assessment of RHI on postoperative day one. The study found no significant effect of RIPC on postoperative RHI [ 43 ]. Apart from the RIPC procedure being initialised in the operating room just prior to surgery, the definition, duration, and number of cycles were identical to our RIPC intervention [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found no significant effect of RIPC on postoperative RHI [ 43 ]. Apart from the RIPC procedure being initialised in the operating room just prior to surgery, the definition, duration, and number of cycles were identical to our RIPC intervention [ 43 ]. While no other studies, to our knowledge, have investigated the effect of RIPC on postoperative endothelial function in patients undergoing non-cardiac surgery, it has been investigated in patients with acute myocardial infarction prior to percutaneous coronary intervention with a significant effect lasting until one week after the intervention [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation